Soil aggregate-mediated microbial responses to long-term warming. (January 2021) - Liu, Xiao Jun Allen; Pold, Grace; Domeignoz-Horta, Luiz A.; Geyer, Kevin M.; Caris, Hannah; Nicolson, Hannah; Kemner, Kenneth M.; Frey, Serita D.; Melillo, Jerry M.; DeAngelis, Kristen M.
Abstract: Soil microbial carbon use efficiency (CUE) is a combination of growth and respiration, which may respond differently to climate change depending on physical protection of soil carbon (C) and its availability to microbes. In a mid-latitude hardwood forest in central Massachusetts, 27 years of soil warming (+5 °C) has resulted in C loss and altered soil organic matter (SOM) quality, yet the underlying mechanisms remain unclear. Here, we hypothesized that long-term warming reduces physical aggregate protection of SOM, microbial CUE, and its temperature sensitivity. Soil was separated into macroaggregate (250–2000 μm) and microaggregate (<250 μm) fractions, and CUE was measured with 18 O enriched water (H2 18 O) in samples incubated at 15 and 25 °C for 24 h. We found that long-term warming reduced soil C and nitrogen concentrations and extracellular enzyme activity in macroaggregates, but did not affect physical protection of SOM. Long-term warming showed little effect on CUE or microbial biomass turnover time because it reduced both growth and respiration. However, CUE was less temperature sensitive in macroaggregates from the warmed compared to the control plots. Our findings suggest that microbial thermal responses to long-term warming occur mostly in soil compartments where SOM is less physically protected and thus more vulnerable to microbial degradation. Highlights: Warming reduced carbon, nitrogen contents and enzyme activity in macroaggregates. Mass of macroaggregates and microaggregates was unaffected by long-term warming. Microbial respiration, but not growth, increased with incubation temperature. Labile carbon content was lower in the warmed soils and in macroaggregates. Warming reduced temperature sensitivity of respiration and carbon use efficiency.